Analyzing structure, process and content in narratives of patients diagnosed with agoraphobia - Gonçalves, Óscar F. (2002)
This research constitutes a first effort testing the possibilities of three rating systems intended to evaluative narrative structure, process and content in psychological disorders. More specifically, the objective of this research is twofold: (1) to explore the reliability of three different rating manuals designed to evaluate, respectively, narrative structure, process and content; (2) to explore the validity of these same manuals in analyzing and discriminating Zenith (i.e., successful) from Nadir (i.e., unsuccessful). Forty patients primarily diagnosed with agoraphobia participated in this study. All the participants followed a protocol interview eliciting two different types of personal narratives: (1) nadir narrative (i.e., unsuccessful life narrative); (2) zenith narrative (i.e., successful life narrative). All the narratives were transcribed for further analysis using three coding manuals for the analysis of narrative structure, process and content. The results found show: (1) a high level of inter-rater reliability for both, each individual dimension of the three rating manuals as well as for the total scores; (2) a high level of internal consistency for each manual both in terms of intercategory correlation coefficients and alpha Cronbach scores; (3) the manuals were effective in discriminating the participants narratives in terms of narrative structure, process and content; (4) Zenith and Nadir narratives did not differ in terms of narrative structure, process and content, with the single exception of the objectifying dimension from the process/ complexity rating manual, showing that agoraphobic patients tend to objectify significantly more in Nadir narratives than in Zenith narratives.